Comparative effects of organic and inorganic fertilizers on the growth performance of chilli pepper (capsicum annum l.) - George, Tubominayesima Stephen; Onwugbuta-Enyi, Jane Akaja (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
Plastic pot experiments were conducted to compare the effects of organic and inorganic fertilizers on the growth of Capsicum annum L. at Ignatius Ajuru University of Education, Rumuolumeni, Port Harcourt. The treatments were three (3) organic fertilizers (poultry, cow dung, household waste and inorganic fertilizers (NPK 10:10:10). Organic and inorganic fertilizers were applied at the rate of 20,40, 60g with 0 as control. The experiment was set up in a Completely Randomized Design (CRD) with four (4) replications. Data generated were analysed using Analysis of Variance (ANOVA), and means were compared using the least significant difference (LSD) at a 0.05% level of probability. Plant growth and development were assessed using plant height, stem girth, root length, leaf area and the total number of fruits. Results obtained showed that household wastes produced the tallest plants with a mean of 34.4±4.2cm, at 40 and 60g rates; longest stem girth (3.9±0.5cm), at 20g, longest root length (18.3±4.8cm) at 60g respectively. Poultry waste produced the highest broad-leaved area, at 60g (97.08±.63cm) with 28 fruits. Based on the data analysed, household and poultry waste resulted in increased plant height, stem girth, root length, broad-leaved area, and the total number of fruit as compared to cow dung, NPK and control. It is, therefore, recommended that household and poultry wastes be used as a better option in the cultivation of Capsicum annum by farmers.